1984
DOI: 10.1152/jappl.1984.57.6.1640
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pulmonary congestion on airway reactivity to histamine aerosol in dogs

Abstract: We examined the effect of acute pulmonary vascular congestion on bronchial reactivity in dogs in a standard challenge protocol. Airway responsiveness to histamine whose concentration was varied in a stepwise incremental fashion was assessed from changes in pulmonary resistance (RL) and dynamic compliance (Cdyn) in 10 anesthetized dogs. Brief acute pulmonary congestion was created by inflating a balloon placed in the left atrium to raise left atrial pressure to 20-30 cmH2O for 1 min. Pulmonary congestion did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1

Year Published

1990
1990
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 0 publications
1
13
1
Order By: Relevance
“…In dogs acute pulmonary vascular congestion renders the bronchi hyperresponsive to histamine through vagal reflexes [3]. Congestion and edema of bronchial wall have been suggested as possible mechanisms of bronchial hyperresponsiveness by Cabanes et al [2] on the basis of the protective effect of methoxamine on methacholine-induced bronchoconstriction in patients with im paired left ventricular function.…”
Section: Introductionmentioning
confidence: 99%
“…In dogs acute pulmonary vascular congestion renders the bronchi hyperresponsive to histamine through vagal reflexes [3]. Congestion and edema of bronchial wall have been suggested as possible mechanisms of bronchial hyperresponsiveness by Cabanes et al [2] on the basis of the protective effect of methoxamine on methacholine-induced bronchoconstriction in patients with im paired left ventricular function.…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of such POSTPHT, numerous clinical studies have demonstrated a compromised lung function and the development of BHR both in patients with an impaired left ventricular function [1,[7][8][9] or valvular diseases [10]. Experimental models have been utilized successfully in various animal species in order to characterize the pulmonary consequences of acute POSTPHT [2,[11][12][13] and have contributed considerably to a better understanding of this disorder.…”
mentioning
confidence: 99%
“…Pulmonary artery wedge pressure during mild exercise increases markedly in patients with COPD even though they have no overt left heart disease and no increase in the esophageal pressure as a reflection of mean intrathoracic pressure (Butler et al 1988). Vascular congestion is reported as one of the factors that causes bronchoconstriction and ventilation-perfusion unevenness (Kikuchi et al 1984). Physical signs are those of chronic obstructive airflow disease with widespread airway adventitial sounds such as rhonchi or wheeze, the severity of the latter depending upon whether the precipitating deterioration is predominantly asthmatic or not.…”
Section: Resultsmentioning
confidence: 99%